Nigeria - State of Lagos : State Financial Accountability Assessment - World Bank (Washington, DC, 2013)
The main elements of government financial management systems are present in Lagos State. They include budgeting, internal control, accounting, Treasury management, financial reporting, and auditing arrangements. The current Lagos State Government is reform-oriented. In keeping with this orientation, it already has taken some giant steps to improve FM systems in the State. An Oracle-based financial management system has been procured and is being installed. It will improve the State's budgeting, accounting, and financial reporting arrangements. The computerized system will put the State of Lagos clearly ahead of most, if not all, State Governments in Nigeria in FM system modernization. The State Government has developed and implemented procedures to improve the effectiveness of tax revenue collection and monitoring. These efforts have begun to show marked results. Additional financial management staff has been recruited; many of them are professionally qualified. In addition, accounts that were in arrears for several years under the Military have been brought up to date. However, some critical aspects of financial management still need to be addressed. Financial accountability is weak, and significant risks of misuse of funds and waste remain. There are also risks that financial records do not present accurate records of transactions. The risk arising from the outside environment also is assessed as high. Given such an environment, strong controls are necessary to prevent wrongful use of public funds; but, in reality, controls are weak, leaving dangerous gaps in FM and accountability systems. The overall risk to public funds therefore is assessed as high. The main recommendation made in the report is that the State of Lagos should strengthen its public financial management arrangements. Specific actions regarding the legal framework, budgetary control, debt management, financial reporting and fiscal transparency, internal controls, external audit, Parliamentary oversight, global computerizations, and management of public enterprises are proposed.